Media image of corruption in the private sector - Jana Marković (Revija za kriminologiju i krivično pravo)
Corruption has long existed as a all-around social phenomenon characterized by complexity and action that takes place "far from the public eye". Various forms of corrupt activity, regardless of whether they are manifested in the public or private sector, threaten the values of every society. Although originally associated with the state and (its) officials with public powers, there is more and more talk about corporate corruption that manifests itself in the private sector or the area of overlap between the public and private spheres. The author's premise is that the media plays a crucial role in combating corruption through the media discourse that shapes public perception and reality of this issue. The objective is to outline the characteristics of the media portrayal of corruption. The discussion focuses on the media's contribution to fighting corruption and also addresses the obstacles that hinder media coverage, resulting in a distorted representation of corruption.